Thermal and Ion Transport Studies in FeSO4.7H2O - Mauli Dwivedi, Mrigank; Pandey, Kamlesh (Asian Journal of Chemistry, 2012)
The proton transport in ferrous sulphate has been established using different techniques like thin layer chromatography, differential thermal analysis/thermal gravimetric analysis, polarization, coulometry and electrical conductivity measurements. The possible charge cariers in hydrogen bonded or hydrate materials are protons (i.e., H+ or OH–) which are generated on the electrolysis of the water of crystallization and provide the protonic conductions.